ANALISIS OPTIMALISASI PENJUALAN PRODUK CIRENG MENGGUNAKAN METODE GRAFIK LINIER PROGRAMING - Nurlinda Nurlinda; Nabila Andini Putri, Gerda Malanesia Bosway, Elvin Suberjun, Frialin Gracia Kadiwaru, Heru Sutejo (CV. ADIBA AISHA AMIRA, 2025)
In the world of micro and small enterprises, limited resources such as cost, time, and labor are major obstacles in production planning. This study aims to determine an optimal production strategy to maximize the profit from the sale of two types of cireng products, namely chicken- filled cireng and meatball-filled cireng, using a linear programming approach. The methods employed include the graphical method and the QM for Windows software, each applied to solve a mathematical model based on real data from a small-scale business. The analysis results show that the optimal production combination is achieved by producing 1.28 kg of chicken-filled cireng dough and 3.08 kg of meatball-filled cireng dough, yielding a maximum profit of Idr269,240. The graphical method and QM for Windows produced consistent solutions, indicating that linear programming can be an effective and practical tool for micro and small business owners in making production decisions. This approach is expected to be widely adopted by small business sectors, particularly in the processed food industry, to improve production efficiency and business competitiveness